2019
DOI: 10.1136/thoraxjnl-2018-212603
|View full text |Cite
|
Sign up to set email alerts
|

The FMS-like tyrosine kinase-3 ligand/lung dendritic cell axis contributes to regulation of pulmonary fibrosis

Abstract: RationaleDendritic cells (DC) accumulate in the lungs of patients with idiopathic lung fibrosis, but their pathogenetic relevance is poorly defined.ObjectivesTo assess the role of the FMS-like tyrosine kinase-3 ligand (Flt3L)-lung dendritic cell axis in lung fibrosis.Measurements and main resultsWe demonstrate in a model of adenoviral gene transfer of active TGF-β1 that established lung fibrosis was accompanied by elevated serum Flt3L levels and subsequent accumulation of CD11bpos DC in the lungs of mice. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In the murine bleomycin skin and lung fibrosis models, reduction of pDCs results in decreased inflammation and fibrosis, indicating their potential as a therapeutic target in fibrosis ( 59 ). Murine studies and the accumulation of conventional dendritic cells (cDCs) in the BAL fluid of patients with IPF have implicated cDC dysfunction in the pathogenesis of IPF, however the role of pDCs in IPF is much less defined ( 62 , 63 ). In our analysis, although pDCs were recovered from the lung at similar frequencies for both IPF and SSc-ILD, the SSc-ILD pDCs were more transcriptionally active, expressed greater type 1 interferon receptor, and upregulation of multiple cellular stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the murine bleomycin skin and lung fibrosis models, reduction of pDCs results in decreased inflammation and fibrosis, indicating their potential as a therapeutic target in fibrosis ( 59 ). Murine studies and the accumulation of conventional dendritic cells (cDCs) in the BAL fluid of patients with IPF have implicated cDC dysfunction in the pathogenesis of IPF, however the role of pDCs in IPF is much less defined ( 62 , 63 ). In our analysis, although pDCs were recovered from the lung at similar frequencies for both IPF and SSc-ILD, the SSc-ILD pDCs were more transcriptionally active, expressed greater type 1 interferon receptor, and upregulation of multiple cellular stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial published in 2015, the DC-specific growth factor Flt3L was found to increase cDC1 and cDC2 cell populations' precursors in bone marrow biopsies and peripheral blood samples from healthy volunteers (64). Following this finding, Flt3L has further been shown to be up-regulated in the serum and lung tissue of IPF patients, likely contributing to the accumulation of lung DCs during pulmonary fibrogenesis (65).…”
Section: The Role Of Dcs In Ipf Pathogenesismentioning
confidence: 92%
“…Accordingly, recent clinical trials have explored the safety and efficacy of recombinant human Flt3L in healthy volunteers and cancer therapy to trigger DC expansion in humans (79)(80)(81). Interestingly, recombinant Flt3L increased the numbers of CD11b + DCs, reducing lung fibrosis in wild-type (WT) mice exposed to AdTGF-beta1 (65).…”
Section: The Way Forward: Similarities With Cancer Biology and Rationmentioning
confidence: 99%
“…Selective depletion of lung DCs markedly exacerbated lung fibrosis in mice, suggesting a protective role of lung DCs in fibrogenesis [ 59 ]. Furthermore, increased mobilization of lung CD11b + DC regulated pulmonary fibrosis development in mice [ 60 ]. These studies have suggested the potential of DC-based immunotherapy for the treatment of lung fibrosis.…”
Section: Innate Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%